Tingkat Stres Orang Tua Sebagai Faktor Risiko Masalah Perkembangan Emosional pada Anak Prasekolah - Wulandari, Elfitra Dwi; Yuswanto, Tri Johan Agus Agus; Suprapti, Suprapti; Kostania, Gita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
The emotional development of preschool children plays a crucial role in their overall development and can be influenced by various factors, one of which is the level of stress experienced by parents. The purpose of this research was to analyze the correlation between parental stress levels and the emotional development of preschool children. This research design was cross-sectional, involving parents and preschool children. Parental stress levels were measured using the Perceived Stress Scale, while children's emotional development was measured using the Emotional Behavior Problems Questionnaire. Furthermore, the hypothesis was verified using a Spearman correlation test. The analysis showed a Rho of 0.544 and a p-value of <0.001, indicating a correlation between parental stress levels and preschool children's emotional development. Based on these results, it can be concluded that parental stress is a risk factor for problems in preschool children's emotional development.Keywords: preschool children; emotional development; parental stress ABSTRAK Perkembangan emosional anak prasekolah berperan penting dalam keseluruhan perkembangan mereka dan dapat dipengaruhi oleh berbagai faktor, salah satunya adalah tingkat stres yang dialami oleh orang tua. Tujuan riset ini adalah menganalisis korelasi antara tingkat stres orang tua dengan perkembangan emosional anak prasekolah. Desain riset ini cross-sectional, yang melibatkan orang tua dan anak prasekolah. Tingkat stres oran tua tua diukur dengan Perceived Stress Scale, sedangkan perkembangan emosional anak diukur dengan Kuesioner Masalah Perilaku Emosional. Selanjutnya dilakukan pembuktian hipotesis menggunakan uji korelasi Spearma. Hasil analisis menunjukkan Rho adalah 0,544 dan nilai p  adalah <0,001, sehingga ditafsirkan bahwa ada korelasi antara tingkat stres orang tua dengan perkembangan emosional anak prasekolah. Berdasarkan hasil tersebut bisa disimpulkan bahwa stres orang tua merupakan faktor risiko bagi masalah perkembangan emosional anak prasekolah.Kata kunci: anak prasekolah; perkembangan emosional; stres orang tua